2011
DOI: 10.1108/16605371111127279
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable medical tourism in Costa Rica

Abstract: PurposeThe purpose of this paper is to ascertain the relative importance of sustainable tourism practices to medical tourists. Sustainable management practices have become the accepted and appropriate model for tourism. Medical tourists, those who visit a foreign country for a medical procedure unavailable at home due to high costs, timeliness or local laws and customs, are asked how important a set of sustainable management practices are in their experiences. Selected for this study are the Global Sustainable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Such an approach makes one begin to doubt whether this is not just a business. If medical tourism is not going to sustain its development, it will only deepen existing differences and injustices between the richer and poorer Sustainable Medical Tourism: Conceptual Framework, Table 2 Sustainable aspects of the development of medical tourism in terms of previous scientific research Pillars Conclusions from the research Authors Economy Medical tourism development in consolidation of the "Certification in Sustainable Tourism Program" Bristow et al (2011) Possibilities of ineffective use of limited public resources to support the development of the medical tourism industry Johnston and Crooks (2013) Central and Eastern Europe region is a sustainable medical tourism destination choice for the citizens of Western Europe…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an approach makes one begin to doubt whether this is not just a business. If medical tourism is not going to sustain its development, it will only deepen existing differences and injustices between the richer and poorer Sustainable Medical Tourism: Conceptual Framework, Table 2 Sustainable aspects of the development of medical tourism in terms of previous scientific research Pillars Conclusions from the research Authors Economy Medical tourism development in consolidation of the "Certification in Sustainable Tourism Program" Bristow et al (2011) Possibilities of ineffective use of limited public resources to support the development of the medical tourism industry Johnston and Crooks (2013) Central and Eastern Europe region is a sustainable medical tourism destination choice for the citizens of Western Europe…”
Section: Discussionmentioning
confidence: 99%
“…Lubowiecki-Vikuk and Dryglas (2019b) Decreasing public health funding in developing countries that experiment with tourism-related patterns of healthcare system commercialization de Castro et al 2015Governments would have to ensure that tax revenues generated from healthcare tourism are reinvested in healthcare development initiatives Then residents are likely to notice concrete benefits from this sector Yim (2005) Sustainable medical tourism is important because companies and regions that create significant value have a positive economic impact on the development of the tourism sector and the surrounding area Perkumien_ e et al (2019) SocietyAccess to a local community living close to medical tourism services for healthcare Bristow et al (2011) Facilitators' cooperation perspectives in sustainable medical tourism should be highly beneficial for participants and medical tourists Inelmen et al (2015), Perkumien_ e et al 2019, Jackson and Barber (2015) Healthcare tourism has the potential of transferring healthcare problems associated with the developed world to the developing world Vijaya 2010Healthcare systems in EU countries may be more effective for medical tourists than for residents Androutsou and Metaxas (2019) Good quality of treatment, trademarks, famous doctors, and intellectual property as a driver for sustainability in medical tourism Bolos (2013) Environment Ways to properly remove and dispose of medical waste that "threatens local water supplies and the public health of nearby residents"…”
Section: Discussionmentioning
confidence: 99%
“…Islamic standards organizations that operate internationally are the Joint Commission International (JCI) in the U.S, Trent Accreditation Scheme in the U.K (Bristow et al, 2011), the Canadian Council on Health Services Accreditation (CCHSA), Australian Council on Healthcare Standards International (ACHSI) (Woodhead, 2013). For example, the Joint Commission International (JCI) is considered as the global largest accreditation organization in the world (Cochrane, 2014).…”
Section: Need Of Internationalmentioning
confidence: 99%
“…Other than that, the source of motivation for the chosen destinations for health care services is the adventure from the country they were visiting such as the cultural activities that is not available in their home country (Adams et al, 2015). Bristow et al (2011) stated found that the respondents prefer Costa Roca as the first destination of getting the health care services, followed by Mexico and India. But the numbers might differ over the different regions of study.…”
Section: Product Qualitymentioning
confidence: 99%